The Creation Of The Composition Of The Musical Work Of Kemepyar As Representation Of Traditional Music Diversity - Eli Irawati; Warsana Warsana (Journal of World Science, 2024)
The creation of the work "kemepyar" is a response to the typical archipelago food containing many spices, one of which is soto. Soto is made from a variety of spices and spices from all corners of the country, be it in the form of tubers, leaves, grains, and so on. The mixture of various Indonesian spices produces a distinctive taste and makes the body feel warm and fit. This was used as an inspiration for the creation of the artwork entitled Kemepyar.  Kemepyar is a term used by Javanese people to describe a situation that very bright, clear, warm, satisfying, satisfied, and delicious in enjoying a dish of food or drink with a fresh taste. The musical idea of the work comes from Javanese gamelan and Macapat dhandang gula. Musical idioms use Javanese, Balinese, Kalimantan, and Sumatran karawitan. Meanwhile, the medium of cultivation uses gamelan, swipe instruments, saxophone blowing instruments, and tambourines. The purpose of creating this work as a form of response to the social environment, in this case the diversity of spices/spices used in soto dishes as a representation of ethnic diversity and traditional music in Indonesia. This work is useful as a stimulus for Music Composition students to create works derived from the phenomenon of daily life, in this case food. The method of creation was chosen to realize the phenomenon of food diversity of soto spices into the form of musical works. The creation process consists of initial stimulation, idea emergence, exploration, improvisation, formation, and presentation.